Association of PD-1 and PD-L1 Genetic Polymorphyisms with Type 1 Diabetes Susceptibility - Chenyue Qian; Heming Guo; Xiaohong Chen; Aiming Shi; Sicheng Li; Xin Wang; Jie Pan; Chen Fang (Journal of Diabetes Research)
Aims. The programmed death- (PD-) 1/PD-1 ligand (PD-L) pathway plays an important role in regulating T cell activation and maintaining peripheral tolerance. Accumulated studies showed that PD-1/PD-L1 pathway was involved in the development of type 1 diabetes (T1DM). Since the genetic background of type 1 diabetes differs greatly among the different population, we aim to investigate the association of genetic polymorphisms in PD-1 and PD-L1 with T1DM susceptibility in Chinese population. Methods. In total, 166 T1DM patients and 100 healthy controls were enrolled into the study. Genomic DNA was extracted from 4 mL peripheral blood samples collected from each subject. Genotyping of 8 selected SNPs of PD-1 and PD-L1 was carried out by the pyrosequencing PSQ 24 System using PyroMark Gold reagents (QIAGEN). Results. SNP rs4143815 in PD-L1 was significantly associated with T1DM. People carrying the C allele of rs4143815 suffering less risk of T1DM and T1DM patients with G/G genotype showed higher levels of autoantibody (AAB) positive incidence compared with C allele carriers. No significant associations were found in other SNPs. Conclusions. Our results indicate that rs4143815 of PD-L1 is significantly associated with T1DM and may serve as a new biomarker to predict the T1DM susceptibility.